2012
DOI: 10.3390/molecules17077612
|View full text |Cite
|
Sign up to set email alerts
|

Thiadiazines, N,N-Heterocycles of Biological Relevance

Abstract: The 3,5-disubstituted tetrahydro-2H-1,3,5-thiadiazine-2-thione scaffold has found many applications in recent years. This review is aimed at highlighting the most important aspects of these compounds: Synthesis, spectroscopic characterization and biological activities. How the chemical nature of N-substituents influences the overall activity and cytotoxicity profile will also be discussed.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
8
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
4
2
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 27 publications
(8 citation statements)
references
References 41 publications
0
8
0
Order By: Relevance
“…42,68,69 The reaction of NH 3 with CH 2 O and H 2 S has been investigated in more detail: 62 compound 14 was shown to form in mixture with hexamethylenetetramine (25) and the simplest perhydrodithiazine 20 (R = H), and the relative yields of the products depended on the starting material ratio and reaction temperature. Compound 14 could be obtained preparatively with 100% selectivity and high yield by the low temperature reaction of thiomethylating mixture, obtained by bubbling H 2 S through 37% CH 2 O, with aqueous NH 4 Cl solution in the molar ratio of NH 4 Cl : CH 2 O : H 2 S = 10 : (25)(26)(27)(28)(29)(30)(31)(32)(33)(34)(35) : (25-35) (Scheme 8). 70 Compound 14 showed antifungal activity.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…42,68,69 The reaction of NH 3 with CH 2 O and H 2 S has been investigated in more detail: 62 compound 14 was shown to form in mixture with hexamethylenetetramine (25) and the simplest perhydrodithiazine 20 (R = H), and the relative yields of the products depended on the starting material ratio and reaction temperature. Compound 14 could be obtained preparatively with 100% selectivity and high yield by the low temperature reaction of thiomethylating mixture, obtained by bubbling H 2 S through 37% CH 2 O, with aqueous NH 4 Cl solution in the molar ratio of NH 4 Cl : CH 2 O : H 2 S = 10 : (25)(26)(27)(28)(29)(30)(31)(32)(33)(34)(35) : (25-35) (Scheme 8). 70 Compound 14 showed antifungal activity.…”
Section: Methodsmentioning
confidence: 99%
“…Thus, recent publications have reviewed the literature about synthesis 15,35 and biological activity of THTTs. 15,35,36 The chemistry of 1,3,5-thiadiazine has been featured in reviews, 37 devoted to the cyclothiomethylation reaction of primary amines. The synthesis and reactions of isomeric triazolo-1,3,5-thiadiazines was briefly considered in another review.…”
mentioning
confidence: 99%
“…In recent decades, research has indicated that the thiazine ring is an important framework with broad-spectrum biological activity. 1,3,5-Thiadiazines are useful as herbicides (Rodríguez, Suárez, & Albericio, 2012), antimicrobial drugs (El-Shorbagi, 2000), insecticides (Coro, Piñeiro, Monzote, Rodríguez, & Suárez 2011), and miticides (Aboul-Fadl, Hussein, El-Shorbagi, & Khallil, 2002). Most reported 3,4-dihydro-2H-1,3,5-thiadiazines contain ring carbonyl or thiocarbonyl groups: such compounds were previously synthesized (Scheme 1) by (i) treatment of heterocyclic primary thioamides with phenoxycarbonyl isocyanate (Coburn, Ho, & Bronstein, 1982; (ii) cyclization of perchloroethyl isocyanate with thioamides (Eltsov et al, 2008); (iii) reaction of Scheme 1.…”
Section: Public Interest Statementmentioning
confidence: 99%
“…1,3,5-Thiadiazines belong to an important class of heterocyclic compounds. The synthesis of 1,3,5-thiadiazines is successfully realized on the basis of Mannich-type aminomethylation [10][11][12][13]. 1,3,5-Thiadiazines are also of interest due a wide range of biological activity and practically important properties [12,14,15];…”
Section: Graphical Abstractmentioning
confidence: 99%